Interpreting measures of tuberculosis transmission: a case study on the Portuguese population - Lopes, Joao (2015)
Tuberculosis remains a high burden for Human society despite considerable investments in its control. Unique features in the history of infection and transmission dynamics of tuberculosis pose serious limitations on the direct interpretation of surveillance data and call for models that incorporate latent processes and simulate specific interventions.